ANALISIS IMPLEMENTASI MANAJEMEN KEDISIPLINAN SISWA DI SMP NEGERI 2 RUMBIO JAYA KAMPAR - Dahlianis Dahlianis; Hadriana Hadriana; Gimin Gimin (Universitas Riau, 2020)
Discipline is one of the things that must be upheld in school because discipline is the key to school success. The existence of high discipline can be one of the capital for schools to achieve the expected goals. In order to enforce this discipline, it requires discipline management based on theories reflected in the functions of management consisting of planning, organizing, implementing, and supervising to determine and achieve the targets that have been determined through the utilization of human resources and other resources. This research is a type of qualitative research, research that tends to handle research problems that require exploration, where knowledge of the problem is still limited, about a detailed understanding of central phenomena. With data collection techniques done with Interviews, observation and documentation. The data processing procedure is done by triangulation technique, checking informant, and examination of data. The result of the research shows that 1) the planning on the discipline management work program has been done well but the implementation can’t run consistently, 2) the organization of discipline management has been well established, but policy making in the determination of sanctions can’t be taken by the highest policy holders in the organizational structure of management discipline, 3) the implementation management function is limited to the process and not in the field but in the final sanction can’t be implemented, 4) the supervision has been done well by the leader but in the evaluation process cannot be implemented because basically the school already know the cause of management evaluation can be done.